Validation of the Rational and Experiential Multimodal Inventory in the Italian Context. Issue 1 (August 2016) - Monacis, Lucia; de Palo, Valeria; Di Nuovo, Santo; Sinatra, Maria
The unfavorable relations of the Rational and Experiential Inventory Experiential scale with objective criterion measures and its limited content validity led Norris and Epstein to propose a more content-valid measure of the experiential thinking style, the Rational and Experiential Multimodal Inventory (REIm), in order to assess the several facets of a broader experiential system consisting of interrelated components. This study aimed to provide the Italian validation of the inventory by examining its psychometric features, its factor structure (Study 1, N  = 545), and its convergent and discriminant validity (Study 2, N  = 257). Study 1 supported the 2- and 4-factor solutions, and multi-group analyses confirmed the invariance measurement across age and gender for both models. Study 2 provided evidence for both the convergent validity by supporting the theoretical associations among Rational and Experiential Multimodal Inventory scores and similar and related measures, and the discriminant validity by showing associations between the two thinking styles and a different but conceptually related construct, i.e., identity formation. No associations between Rational and Experiential Multimodal Inventory scores and social desirability were found. The Italian version of the Rational and Experiential Multimodal Inventory showed satisfactory psychometric properties, thus confirming its validity.